2016
DOI: 10.3329/bjar.v41i2.28229
|View full text |Cite
|
Sign up to set email alerts
|

Variability and path co-efficient for yield and yield components in rice

Abstract: Twenty five rice varieties were evaluated for their variability with regard to yield and yield components. Estimates of heritability and genetic advance as per cent mean were also obtained for the above traits. In addition, studies on character associations and path co-efficients were also undertaken. The results revealed high variability, heritability and genetic advance as per cent mean for productive tillers per plant, number of tillers per plant, number of grains per panicle and number of filled grains per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 10 publications
24
9
0
Order By: Relevance
“…The high heritability values of the considered traits in the present study indicated that those were less influenced by the environment and thus help in effective selection of the traits based on the phenotypic expression by adopting simple selection method and suggested the scope of genetic improvement. Similar results for 100 seed weight, number of unfilled grains per panicle and number of effective tillers per plant were earlier recorded by Gour et al (2017), Sameera et al (2016) and Sumnath et al (2017) respectively.…”
Section: Resultssupporting
confidence: 89%
“…The high heritability values of the considered traits in the present study indicated that those were less influenced by the environment and thus help in effective selection of the traits based on the phenotypic expression by adopting simple selection method and suggested the scope of genetic improvement. Similar results for 100 seed weight, number of unfilled grains per panicle and number of effective tillers per plant were earlier recorded by Gour et al (2017), Sameera et al (2016) and Sumnath et al (2017) respectively.…”
Section: Resultssupporting
confidence: 89%
“…These results were confirmed with the finding of Rajender et al, (2013) for days to 50% flowering, plant height, Sravan et al, (2012) for days to 50% flowering, number of productive tillers per plant and number of grains per panicle, Sameera et al, (2015) for plant height and panicle length, Pandey et al, (2012) for number of grains per panicle and seed yield per plant. Heritability is a measure of extent of phenotypic variation caused by the action of genes.…”
Section: Resultssupporting
confidence: 82%
“…These results were confirmed with the finding of Rajender et al, (2013) for days to 50% flowering, Patel et al, (2014) plant height, Sravan et al, (2012) for number of grains per panicle, Sameera et al, (2015) for number of productive tillers, seed yield per plant. Pandey et al, (2012) for seed yield per plant, Singh et al, (2011) for days to 50% flowering, panicle length and number of grains per panicle.…”
supporting
confidence: 82%
“…The heritability estimate for this trait was very high (98.9) with high genetic advance as per cent of mean (62.84).The similar results were observed by Mohan et al, (2015) and Sameera et al, (2015)for high GCV and PCV, Karande et al, (2015) for high heritability and for high genetic advance as percent of mean. …”
Section: Number Of Filled Grains Per Paniclesupporting
confidence: 76%
“…The observed heritability estimate for this trait was high (91.9) while genetic advance as per cent of mean (21.42) were moderate. The results were conformity with Sameera et al, (2015) for moderate GCV and PCV and Gampala et al, (2015) for high heritability and Islam et al, (2015) for moderate genetic advance as percent of mean.…”
Section: Days To 50 Per Cent Floweringsupporting
confidence: 58%